PERSEPSI NASABAH TENTANG LAYANAN PERBANKAN: PENGARUH SERVICE FAILURE DAN STRATEGI SERVICE RECOVERY TERHADAP BEHAVIORAL INTENTIONS - Yuli Liestyana (University of Merdeka Malang, 2009)
The research was conducted to verify the ability of service quality and service recoverystrategy to predict behavioral intentions in the banking industry. A survey questionnaire wasdeveloped, then it was distributed to 150 customers of banks in Yogyakarta. Data was analyzedusing multiple regression analysis. The results provided support for hypothesis of the negativeeffect of service failure and positive effect of recovery strategy on behavioral intentions.